ANALISIS KEMUDAHAN, HAMBATAN, DAN RISIKO PERUSAHAAN DI NEGARA INDONESIA, CHINA, SINGAPURA, DAN JEPANG - Yuswardi Yuswardi; Renza Fahlevi; Jesslyn Clorina; Shereen Shereen; Fiona Fiona; Shely Juniarty; Jacky Gunadi (Jurnal Ekonomi dan Bisnis (EK dan BI), 2023)
Globalization has encouraged companies to expand their business abroad, and one option is to expand to the Asian continent. The purpose of this research is to find out what are the ease, barriers, and risks of doing business in several Asian countries with fast economic growth, namely China, Japan, Singapore, and Indonesia. The research method used is a qualitative method and the technique used is a literature study. The results found are that each country has different easiness, obstacles, and risks for doing business. Some of the ease is Indonesia which is superior in natural resources and strategic location, China which has skilled human resources and adequate infrastructure, Japan which has a high demand for products and well-structured work processes, and Singapore which has stricter regulations. free to do business. On the other hand, some of the obstacles are Indonesia having complicated permits and inadequate infrastructure, China which is constrained by language and employing employees having to go through organizations, Japan with a high bureaucracy and tax system, and Singapore with its public wage regulations and communication media that are limited. Each of the risks lies in inadequate infrastructure in Indonesia, markets that are difficult to access in China, a difficult bureaucratic system in Japan, and a complicated government system in Singapore.